Politics and Society in Dashiell Hammett’s The Maltese Falcon - Zumoff, Jacob A. (AmLit)
This essay examines the vision of society presented in Dashiell Hammett’s The Maltese Falcon (1930). In contrast to critics who argue that Hammett brought a Marxist perspective to the novel, reflecting his support to the Communist Party later in the decade, this current article argues that The Maltese Falcon presents a vision of society with no fundamental order or meaning, in which all rules are arbitrary, and in which every attempt to present a grand narrative fails. This nihilist conception of society is in keeping with the rise of modernism and reflects the shift from a rural, agricultural, traditionalist society to an urban, industrial one. It is not, however, a Marxist view.